Jurnal Prediksi Nilai Ekspor Indonesia Menggunakan Metode Artificial Neural Network (ANN) - Rahul Sinurat; Arion Tampubolon; Irene Lestaria sinaga; Monica Sari Batubara; Novita sari siagian; jaya tatahardinata (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2026)
Exports are one of the main indicators of Indonesia's economic growth. To assist in planning and policymaking, accurate prediction techniques are needed because various factors influence export value fluctuations. Using the Artificial Neural Network (ANN) method, this study aims to predict Indonesia's export value. The data used comes from official sources and is processed through preprocessing, normalization, and the division of training and test data. To predict export value, an ANN model is built and trained to recognize patterns of relationships between data. The results show that the ANN method can predict Indonesia's export value with a high degree of accuracy. Therefore, the ANN method can be used as an effective alternative for predicting export value and assisting economic decision-making